Effect perform of smell to raises of acti١ities fitness - nuha (Iraqi National Journal of Nursing Specialties, 2023)
The aim of study to know to perform of smell to raises level of activities fitness, In it study using experimental research at the design of controlling group and experimental group , And displays the results. The experimental variable take place effect by physiology response in rises level of activities fimess, and Seeds the pupils used with them Perfume in the level of activities fitness, the Recommendation, necessary important in sport in the motor learning and teaching and teaching and that Perfume to Percolate to pupils and Players in the closes Rome.